2023
DOI: 10.3390/met13091618
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Behavior and Corrosion Properties of Stirred Zone in FSWed AA5083 Al-Mg Alloy after Sensitization

Wenbin Gao,
Jiaao Ning,
Xiaoyan Gu
et al.

Abstract: This paper investigated the Mg-rich phase precipitation behavior and the corrosion performance throughout the thickness direction within the stirred zone (SZ) of friction stir welded (FSW) AA5083 alloy after 175 °C/100 h sensitization. For the as-welded SZ, the recrystallized grain size gradually decreased from the top surface (5.5 μm) to the bottom (3.7 μm). The top and bottom of the SZ maintained relatively high levels of deformed grains and accumulated strain induced by either shoulder pressing or pin stirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Similar descriptions can be found in ref. [30]. Finally, T-Mg 32 (Al,Zn) 49 dots also form at grain boundaries, contributing to an increased HTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar descriptions can be found in ref. [30]. Finally, T-Mg 32 (Al,Zn) 49 dots also form at grain boundaries, contributing to an increased HTS.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the microstructural evidence, this study observed that when a 5083 alloy was subjected to shrinkage-induced thermal stress, the inherently brittle fishbone-shaped IMCs turned into hot tearing nucleation points and fractured [Supplementary Figure S3] (see Supplementary Materials). Once hot tearing had occurred, the continuous-phase Al3Mg2 along the interdendritic spaces became a medium for transmitting and promoting crack growth (e.g., the distribution of Al3Mg2 shown in [Supplementary Figure S4] (see Supplementary Materials)), which may be similar to the role of Al3Mg2 in friction stir welding [30]. Moreover, due to the widely distributed fishbone-shaped α-Al15(Fe,Mn)3Si2 in 5b, continuous fractures such as local pore clusters (Figure 10f) or elongated irregular fracture patterns (Figure 10d) emerged upon crack expansion.…”
Section: Influence Of Compositional Variation On Microstructurementioning
confidence: 96%
“…Mechanical properties in the welding region can be changed by the selected welding technologies, especially when dissimilar materials are involved [21][22][23][24][25]. The mechanical properties, mainly yield strength and tensile strength, generally decrease due to precipitate dissolutions in FSW of aluminum alloys [26][27][28][29]. In FSW of dissimilar metals, changes in mechanical properties becomes more complex [30].…”
Section: Introductionmentioning
confidence: 99%